2020
DOI: 10.15537/smj.2020.2.24885
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-1,6-bisphosphatase deficiency with confirmed molecular diagnosis

Abstract: Fructose-1,6-bisphosphatase deficiency with confirmed molecular diagnosis. An important cause of hypoglycemia in children

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In addition to deletion and nonsense mutations that block FBP1 expression, human FBP1 deficiency can be caused by missense mutations (Emecen Sanli et al, 2022; Salih et al, 2020). We stably expressed FBP1 missense mutants in Huh7 cells and found most of them to be poorly expressed and devoid of catalytic activity (Figures 7A and S8A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to deletion and nonsense mutations that block FBP1 expression, human FBP1 deficiency can be caused by missense mutations (Emecen Sanli et al, 2022; Salih et al, 2020). We stably expressed FBP1 missense mutants in Huh7 cells and found most of them to be poorly expressed and devoid of catalytic activity (Figures 7A and S8A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to deletion and nonsense mutations that block FBP1 expression, human FBP1 deficiency can be caused by missense mutations (Emecen Sanli et al, 2022;Salih et al, 2020).…”
Section: A Complex Disrupting Fbp1-derived Peptide Ameliorates Insuli...mentioning
confidence: 99%
See 1 more Smart Citation
“…After literature review, we found different population had its own hotspots. For example, two missense mutations c.841G > A and c.472C > T are reported as the most common alleles in the India and Pakistan population [1,2], c.958G > A and c.986T > C are the most frequent variants in the Southern Brazilian [10], while c.114_119dup is prevalent in Saudi Arabia [13], c.960_961insG and c.490G > A are common in Japan [8,14]. The situation for the Turkish patients is signi cantly different, as the exon 1 deletion (NM_000507.4) is the most common variant and considered as the founder mutation in Turkish FBP1D patients.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Clinical manifestations are characterized by life-threatening episodes of acidosis, hypoglycemia, hyperventilation, convulsion and coma. 2,3 In about half of the cases, the deficiency presents in the 1 st week of life. 4 In infants and young children, episodes are triggered by febrile infections and gastroenteritis if oral food intake decreases.…”
Section: Introductionmentioning
confidence: 99%